POLITIK HUKUM KENOTARIATAN PASCA PERUBAHAN UNDANG-UNDANG JABATAN NOTARIS BAGI NOTARIS DALAM MENJALANKAN JABATANNYA - Arliman S, Laurensius (Dialogia Iuridica, 2018)
Notary is a public official who has the authority to make the authentic act and have other powers, as mentioned in the post of notary regulations or by other rules. That is, the notarial deed relates directly to the value of the dignity of the parties that promise. Appointments are expressed in deed, is the will submitted by the parties. Notary born as a result of legal needs in the community, can be seen by the increasing number of agreements set forth in a notarial deed. Law Politics greatly affect the existence of Notary. It can be seen from the legislation that had been out, to adjust the position of Notary in the running position. With the growing strengthening of existence Notary position, it will bring a better impact to Notary.